1992
DOI: 10.1007/bf00873122
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of 5 day continuous intravenous infusion of 6-thioguanine in patients with recurrent and metastatic squamous cell carcinoma of the head and neck

Abstract: Fifteen patients with recurrent and/or metastatic squamous cell carcinoma of the head and neck received a 5 day continuous I.V. infusion of 6-thioguanine repeated every five weeks. Dose limiting toxicity was primarily hematological with grade III/IV leucopenia and thrombocytopenia seen in seven patients. Nausea and vomiting was moderate and well controlled with antiemetics. No complete or partial responses were observed, with a median time to progression of 58 days and a median survival of 227+ days for the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Thioguanine has not shown efficacy as a single or combined agent in the treatment of solid tumors including colorectal carcinoma [38,39], pancreatic carcinoma [40] and gastric cancer [41] (Table 1). Thioguanine also had very limited effect as a therapy for metastatic squamous cell carcinoma [42], metastatic breast cancer [43] and renal carcinoma [44]. In addition, TG has been tested in both non-small cell lung cancer [45] and recurrent small cell lung cancer [46] but no clinical response was observed in these patients.…”
Section: Oncology and Hematologymentioning
confidence: 99%
“…Thioguanine has not shown efficacy as a single or combined agent in the treatment of solid tumors including colorectal carcinoma [38,39], pancreatic carcinoma [40] and gastric cancer [41] (Table 1). Thioguanine also had very limited effect as a therapy for metastatic squamous cell carcinoma [42], metastatic breast cancer [43] and renal carcinoma [44]. In addition, TG has been tested in both non-small cell lung cancer [45] and recurrent small cell lung cancer [46] but no clinical response was observed in these patients.…”
Section: Oncology and Hematologymentioning
confidence: 99%
“…Kovach et al [13] evaluated a schedule of intravenous 6-TG and found that a dose of 55-65 mg/m 2 given daily for 5 days caused doselimiting myelosuppression without other significant toxicity. This dose schedule was then used over the next decade to treat patients with various solid tumors [14][15][16][17][18][19][20][21][22][23] (Table 2). Minimal antitumor effects were observed, except possibly for the treatment of breast cancer.…”
Section: Do Dose and Schedule Matter?mentioning
confidence: 99%
“…Third, although MTA/6-MP might be expected to substitute for MTA/6-TG in the method described, it does not, perhaps because 6-MP is not as potent as is 6-TG or for other reasons that are not yet known (unpublished data).The optimal dosage and schedule for in vivo experiments with the MTA/6-TG method [15] 88 2 PR Gastric cancer [16] 17 0 Pancreatic cancer [17] 32 2 PR Head and neck cancer [18] 15 0 Non-small cell lung cancer [19] 46 1 PR, 1 CR Small cell lung cancer [20] 19 0 Renal cell cancer [21] 20 0 Breast cancer [22] 23 1 PR, 3 SD Breast cancer [23] 41 2 CR, 4 PR…”
Section: Rationale For Mta Selective Protection Of Normal Tissues and Not Mtap-deficient Tumorsmentioning
confidence: 99%